Diagnostic Accuracy of Doppler Ultrasound in Detecting Tumor Thrombus in Inferior Vena Cava (IVC) in Renal Cell Carcinoma (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine diagnostic accuracy of Doppler Ultrasound in detecting inferior vena cava tumor thrombus in cases presenting with renal cell carcinoma taking histopathology as gold standard. Materials and Method: After informed consent, a total of 125 renal cell carcinoma patients were included in the study. Patients’ demographic data was entered in proforma in each case. Setting: The study was conducted at the Department of Diagnostic Radiology Lahore General Hospital, for a period of six months from 21-05-2014 to 20-11-2014 , Lahore. Research Design: Qualitative , descriptive and cross sectional. Sampling Technique: Convenient/Non probability sampling. All patients underwent Doppler ultrasound to assess the involvement of the inferior vena cava by tumor thrombi. Tumour specimen was sent to hospital pathology department for its histopathological analysis. The results of Doppler ultrasound were conpared with the findings of histopathology as gold standard. Results: The mean age of subjects was 46.80±17.01 years. In this study 73 (58.4%) patients were male and 52 (41.6%) were female. Color Doppler Ultrasound revealed that out of total 125 patients, 91 (72.8%) had positive findings while 34 (27.2%) had negative findings, whereas, according to the results of the histopathology 90 (72.0%) patients showed a positive result while 35 (28.0%) had a negative result. Setting histopathology as a gold standard, the overall diagnostic accuracy of Color Doppler Ultrasound came out to be 91.2% The sensitivity was 94.44% and specificity 82.86% of Color Doppler Ultrasound. The negative and positive predictive values were found as 93.41% and 85.29% respectively. Conclusion: Diagnostic accuracy of Doppler ultrasound is high (sensitivity =94.44% and Specificity = 82.86%) in detecting tumor thrombus in inferior vena cava in cases of renal cell carcinoma by taking histopathological findings as gold standard. Due to good diagnostic accuracy of Coloured Doppler ultrasound it can be used as a preferred investigation to CT scan for accurate diagnosis.
Keywords: Thrombus, renal cell carcinoma, Doppler ultrasound